1959
DOI: 10.1115/1.4008156
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer to Water in Thin Rectangular Channels

Abstract: Heat-transfer coefficients are presented for water flowing vertically in thin rectangular channels (0.1 × 2.5 in.) 18 and 36 in. long and heated electrically around the entire periphery. The range of variables covered is: 65 to 200 psia pressure, 90 to 200 F sub-cooling, and 4 to 50 fps water velocity. Heat-transfer correlations are given for data along the narrow and wide faces of the rectangular test section. Burnout data also are reported with steam blanketing occurring first at the corner of the test secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1964
1964
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The flow appeared turbulent everywhere at this Reynolds number (1.4x10 5 ) apart from transitional instabilities close to the inlet of the duct. A typical peripheral survey of heat transfer is given in Figure 12, where the heat transfer coefficients obtained at each gauge These results support the findings of both Levy et al (12) and Battista and Perlins (13) who found their results were some 15-307 and 10% respectively below circular duct correlations.…”
Section: Circular Ductsupporting
confidence: 84%
“…The flow appeared turbulent everywhere at this Reynolds number (1.4x10 5 ) apart from transitional instabilities close to the inlet of the duct. A typical peripheral survey of heat transfer is given in Figure 12, where the heat transfer coefficients obtained at each gauge These results support the findings of both Levy et al (12) and Battista and Perlins (13) who found their results were some 15-307 and 10% respectively below circular duct correlations.…”
Section: Circular Ductsupporting
confidence: 84%